Obesity - Çakmur, Hülya (IntechOpen, 2020)
The World Health Organization has accepted obesity as a global epidemic. The prevalence of obesity is increasing rapidly in industrialized and developing countries. In many countries, obese and overweight adults make up nearly 50% of the population; furthermore, a quarter of children around the world are overweight and obese. Obesity is a chronic systemic inflammation of the adipose tissue. The mechanism of energy intake and expenditure is a homeostatic process. When the balance is upset in favor of energy intake, the result is excessive fat accumulation, which causes a number of diseases. Therefore, obesity can be defined as a multifactorial and heterogeneous disease that leads to adverse cellular and metabolic effects. The underlying mechanisms of obesity are not well understood, but evidence points to oxidative damage. To combat obesity effectively, its pathogenesis must be clearly understood. An understanding of the molecular mechanisms of obesity and obesity-related diseases could lead to the discovery of new therapies and preventive methods. Improvements in environmental conditions, education, preventative measures for at-risk groups, and promotion of healthy diets and physical activity are effective methods for fighting obesity.